Gender equity: how do the forensic sciences fare? - Ward, Jodie; Johnson, Rebecca N.; Wilson-Wilde, Linzi (Australian journal of forensic sciences, 2019)
Females are underrepresented in science, technology, engineering and mathematics (STEM) at all levels of society. Fewer females are completing STEM school subjects, graduating with STEM degrees, being employed as STEM professionals, and holding senior leadership and academic positions in STEM. However, unlike almost every other STEM discipline, the overall ratio of females is higher in many forensic science disciplines. For our sector, rather than having difficulty in attracting females, the bigger issue is how we retain and promote female talent. This complex issue is exacerbated by: gender pay gaps; family role expectations; lack of visible role models or mentors; discrimination and harassment; and bias during recruitment and promotion practices. We discuss barriers relevant for women in the forensic industry and offer potential solutions. These include flexible work arrangements, sponsorship programmes, and fostering and practising an inclusive workplace culture. Gender equity programmes and exemplar STEM organizations focused on a commitment to gender parity will be explored. Harnessing untapped female talent is as much a social justice issue as employing best practices for improving the quality, diversity and output of our forensic science workforce, and research and innovation strategies.